PENGARUH LIKUIDITAS, KEPUTUSAN INVESTASI, LEVERAGE, PERTUMBUHAN PERUSAHAAN, UKURAN PERUSAHAAN DANSTRUKTUR ASSETSTERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE PERIODE TAHUN 2013-2015 - Vivi Kurniawati Yuliana, 13.05.52.0212; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2018)
This study aims to examine and analyze the influence of Liquidity, Investment Decision, Leverage, Corporate Growth, Company Size and Assets Structure against Corporate Value in Property and Real Estate Company Period 2013-2015 The population in this study are property and real estate companies listed on the BEI during 2013-2015. This research is empirical research by using purposive sampling technique in sampling. The analysis was done by multiple regression using SPSS version 16.00 for windows. The results showed that Liquidity does not affect the value of the company. Investment decisions positively affects the value of the company. Leverage positively affects the company's value. Corporate growth has a positive effect on company value. The size of the firm does not affect the value of the company. The asset structure has no effect on firm value Keywords: Liquidity, Investment Decision, Leverage, Corporate Growth, Company Size and Assets Structure and Corporate Value